Digitalisasi Rantai Pasok Halal: Model Transparansi dan Lacak Balak Produk Herba Lokal Berbasis IoT - Heni Pratiwi (STIKes Ibnu Sina Ajibarang, 2026)
The halal integrity of local herbal products is determined not only by raw materials but also by the entire upstream-to-downstream supply chain process. Risks of cross-contamination and a lack of information transparency often hinder the maintenance of sustained halal assurance. This study aims to design an Internet of Things (IoT)-based halal supply chain digitalization model to enhance transparency and traceability within Indonesia's local herbal industry. The research employs a qualitative-systems engineering approach through a case study of the local herbal product supply chain. The results demonstrate that integrating IoT sensors (such as temperature, humidity, and GPS location sensors) with a centralized data platform enables real-time monitoring of storage and shipping conditions. The model successfully maps Halal Critical Control Points and provides data visibility for producers, regulators, and consumers. The study's implications serve to strengthen the national halal supply chain ecosystem and provide a digital framework for herbal MSMEs to meet sustainable halal certification standards.